Development and performance assessment of 3D-printed tidal turbine blades: Insights from steady flow testing (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This work presents the development, testing, and performance assessment of a novel blade set for a 0.6m diameter lab-scale tidal turbine, designed for operation in the Oxford University flume. The flume has a working section of 10m length, 1.1m width, and 1m height, leading to a high blockage ratio of 25.7% and flow conditions corresponding to a chord-based Reynolds number of approximately 105. The turbine is equipped with a torque-thrust transducer and strain gauges to measure edgewise and flapwise root bending moments [1], allowing detailed characterization of rotor performance under both steady and unsteady loading conditions.The study compares the performance of 3D-printed rotor blades, made using stereolithography (SLA) technology with a ceramic-based resin, and conventionally manufactured CNC-machined aluminium blades. The 3D-printing method ensured watertightness and high structural integrity [2]. Key performance metrics, such as torque, thrust, and bending moments, were analysed to evaluate the hydrodynamic responses of each rotor. To assess flow conditions, a detailed flume characterization was carried out using an Acoustic Doppler Velocimeter (ADV), revealing a velocity variation of less than 2% across the rotor plane under steady flow, and turbulence intensity of approximately 2.4%.Unsteady flow conditions were simulated by placing an adjustable upstream across-stream mounted cylinder, which created diverse velocity profiles by varying its vertical position and distance from the turbine. The tests provided insights into blade loading dynamics under non-uniform inflow conditions, showing phase-averaged blade loading variations exceeding 20%. A phase lag due to the tower shadowing effect, similar to [3], was observed. The adjustable obstacle proved effective in generating shear profiles with varying velocity gradients, suitable for lab-scale tidal turbine testing. Compared to previous methods using meshes and grids, the turbulence intensity developed in the obstacle’s velocity deficit region—corresponding to the bottom swept area—was higher at 10%, compared to the 4% reported by Magnier et al. [3].The performance comparison between the 3D-printed rotor and the conventional rotor showed excellent agreement in key metrics. However, the results emphasize the need for careful handling and quality control when using rapid prototyping techniques. The flapwise bending moment was found to be sensitive to blade misalignment in both cases, with the 3D-printed rotor requiring more precise adjustments and occasional post-processing to ensure proper alignment. This research demonstrates the potential of 3D printing for lab-scale tidal turbine blades. The stereolithography process reduced manufacturing time from three months to just 48 hours, achieving a cost saving by a factor of 10 compared to traditional CNC machining, while maintaining a high-quality surface finish. Although careful alignment is necessary, simple in-lab post-processing steps can significantly reduce variation. The rapid manufacturing turnaround time facilitated by 3D printing enables the verification of novel design ideas and rapid modifications to blade geometry, accelerating iterative development.